Redescription of Ceratothoa carinata (Bianconi, 1869) and Ceratothoa oxyrrhynchaena Koelbel, 1878 (Crustacea: Isopoda: Cymothoidae), buccal-attaching fish parasites new to Australia - Martin, Melissa B.; Bruce, Niel L.; Nowak, Barbara F. (Zootaxa, 2013)
Ceratothoa carinata (Bianconi, 1869) and Ceratothoa oxyrrhynchaena Koelbel, 1878 are recorded for the first time from Australia and redescribed. Ceratothoa curvicauda Nunomura, 2006 is synonymised with Ceratothoa carinata. Brief ac-counts are given on the distribution and hosts of these species.